Materials, technological status, and fundamentals of PEM fuel cells – A review - Wang, Yun; Ruiz Diaz, Daniela Fernanda; Chen, Ken S.; Wang, Zhe; Adroher, Xavier Cordobes (Materials today (Kidlington, England), 2020)
[Display omitted] PEM (Polymer Electrolyte Membrane) fuel cells have the potential to reduce our energy use, pollutant emissions, and dependence on fossil fuels. In the past decade, significant advances have been achieved for commercializing the technology. For example, several PEM fuel cell buses are currently rated at the technical readiness stage of full-scale validation in realistic driving environments and have met or closely met the ultimate 25,000-h target set by the U.S. Department of Energy. So far, Toyota has sold more than 4000 Mirai PEM fuel cell vehicles (FCVs). Over 30 hydrogen gas stations are being operated throughout the U.S. and over 60 in Germany. In this review, we cover the material, design, fundamental, and manufacturing aspects of PEM fuel cells with a focus on the portable, automobile, airplane, and space applications that require careful consideration in system design and materials. The technological status and challenges faced by PEM fuel cells toward their commercialization in these applications are described and explained. Fundamental issues that are key to fuel cell design, operational control, and material development, such as water and thermal management, dynamic operation, cold start, channel two-phase flow, and low-humidity operation, are discussed. Fuels and fuel tanks pertinent to PEM fuel cells are briefly evaluated. The objective of this review is three fold: (1) to present the latest status of PEM fuel cell technology development and applications in the portable and transportation power through an overview of the state of the art and most recent technological advances; (2) to describe materials and water/thermal transport management for fuel cell design and operational control; and (3) to outline major challenges in the technology development and the needs for fundamental research for the near future and prior to fuel cell world-wide deployment.